Study of kinetics, isotherms and thermodynamics of lead adsorption from aqueous solutions using Lignocellulose Nano-fibers (LCNFs) - S. Rastgar; H. Rezaei; H. Yousefi (Environmental Resources Research, 2020)
The surface adsorption of heavy metals in effluents with nanoparticles is today asuitable method for effluents treatment. In the present study, lignocellulose nano-fibers(LCNFs) were used as natural adsorbent for lead adsorption. The aim was to evaluate leadadsorption using adsorption isotherms, kinetics and thermodynamics. Fourier TransformInfrared Spectroscopy (FT-IR) and Transmission Electron Microscopy (TEM) wereemployed to determine the chemical and structural properties of this adsorbent. To studythe adsorption isotherm, two-parameter models of Langmuir, Freundlich, Temkin, andDubinin–Radushkevich were compared and three-parameter models of Redlich-Petersonand Sips and maximum correlation coefficient (R2) were selected as the best isothermmodel for lead adsorption, which was obtained for the Langmuir model at 0.9997 and theRedlich-Peterson model at 0.9338. Therefore, the data were consistent with both models butwere better described by the Langmuir model, indicating homogeneity of the adsorbentsurface. In addition, reaction kinetic models, including pseudo-zero-order, pseudo-firstorder, pseudo-second-order and pseudo-third-order as well as the diffusion kinetic modelsincluding intra-particle diffusion and Elovich were investigated for adsorption reaction. Themaximum correlation coefficient (R2=1) was related to the pseudo-second-order model;therefore, the lead adsorption by LCNFs was of a chemical type. The results obtained fromthe calculation of thermodynamic parameters such as Gibbs free energy (ΔG), enthalpy(ΔH◦), and entropy (ΔS◦) respectively showed spontaneity, exothermicity, and increasedirregularities of the reaction. This study showed that LCNF is suitable for the adsorption oflead and as such could be used as a cost-effective adsorbent in the process of industrialwastewater treatment.